2017
DOI: 10.1016/s2215-0366(17)30426-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of behavioural activation with guided self-help for treatment of depression in adults with intellectual disabilities: a randomised controlled trial

Abstract: SummaryBackgroundPsychological therapies are first-line interventions for depression, but existing provision is not accessible for many adults with intellectual disabilities. We investigated the clinical and cost-effectiveness of a behavioural activation intervention (BeatIt) for people with intellectual disabilities and depression. BeatIt was compared with a guided self-help intervention (StepUp).MethodsWe did a multicentre, single-blind, randomised, controlled trial with follow-up at 4 months and 12 months a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(90 citation statements)
references
References 31 publications
3
84
1
2
Order By: Relevance
“…The materials were not developed with people with associated intellectual disability in mind as this was not part of the commissioning brief and recent research has reported successful adaptation of BA for adults with intellectual disability. 71…”
Section: Chapter 5 Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The materials were not developed with people with associated intellectual disability in mind as this was not part of the commissioning brief and recent research has reported successful adaptation of BA for adults with intellectual disability. 71…”
Section: Chapter 5 Discussionmentioning
confidence: 99%
“…Transcripts and field notes were imported into NVivo version 10 software (QSR International, Warrington, UK) for analysis. 71…”
Section: Interview Conductmentioning
confidence: 99%
“…In the current paper, the present authors explore the experiences of adults with intellectual disabilities randomized to one of two psychological interventions for depression; Behavioural Activation or Guided Self‐Help, using a psycho‐educational approach. This was a component of a RCT whose primary objective was to compare the clinical and cost‐effectiveness of Behavioural Activation versus Guided Self‐Help for the treatment of depressive symptoms in adults with intellectual disabilities (Jahoda, Hastings, et al, ). Both interventions were adapted to be suitable for adults with mild and moderate intellectual disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the Lancet Psychiatry, Jahoda et al 1 present the findings of a rigorous UK based multicentre randomised controlled trial of behavioural activation (BA; Beat it) vs active control (Step up) for people with mild to moderate intellectual disabilities and depression.…”
Section: Angela Hassiotis Rory Sheehan Marc Serfatymentioning
confidence: 99%